Education and Assistance for Pregnant Women in Preparing for Safe Delivery to Reduce the Risk of Pregnancy Complications in Health Prone Areas Trimulya Village - Sri Wahyuni; Deddy S Razak; Erni; Agnes Ratna Saputri; A. Wardah Muzfah (CV. Get Press Indonesia, 2025)
Background. One of the main barriers to antenatal care is poor knowledge about pregnancy danger signs and the importance of regular ANC visits. This study used a descriptive qualitative approach with a Community-Based Participatory Research (CBPR) design to describe and evaluate the effectiveness of educational activities and assistance for pregnant women in preparing for safe childbirth in health-prone areas. Methods. Data were collected through participatory observation, in-depth interviews, and focus group discussions (FGDs) with pregnant women, health cadres, and local medical personnel. Pre- and postintervention evaluations were conducted using questionnaires that measured changes in pregnant women's knowledge, readiness, and anxiety levels towards childbirth. Results. After the educational intervention, there was a significant increase in the readiness of pregnant women to face childbirth, with the average score increasing from 46.1 before the intervention to 79.2 after the intervention. The level of anxiety decreased from an average score of 71.5 to 43.9. Maternal knowledge about planning for delivery places increased from 49.3 to 81.5 after the education intervention. Husband/family participation in childbirth preparation increased from a mean score of 38.7 to 72.0 after the program. Conclusions. The educational and mentoring program implemented at the community level has shown effectiveness in increasing knowledge and readiness, as well as reducing anxiety. It is recommended that this program be integrated into the primary health care system and supported by policies that encourage active family participation in maternal and child health.